2022
DOI: 10.1002/nbm.4743
|View full text |Cite
|
Sign up to set email alerts
|

Contrast agent‐free state‐of‐the‐art magnetic resonance imaging on cerebral small vessel disease – Part 2: Diffusion tensor imaging and functional magnetic resonance imaging

Abstract: We included 124 full-text articles that evaluated the DTI additional contributions compared with conventional MRI, brain structural networks, DTI markers, and their relation with cSVD. We also included 28 studies on cSVD-related alterations in functional brain networks assessed by task-based and RS fMRI. Table 1 shows a summary of the main findings. 2 of 17 da SILVA ET AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 189 publications
0
8
0
Order By: Relevance
“…However, Brandhofe and colleagues found that the T2 relaxation time of NAWM was associated with cognition in CSVD patients, which the FA and MD of the NAWM failed to achieve 44 . More recently, newer acquisitions and models such as the free‐water (FW) model have shown greater associations with WM injury and cognitive impairment, as compared to the traditional DTI measures 43 . The development of vessel wall imaging (VWI) allows detailed evaluation of the vessel wall and lumen in a single image setting, enabling the visualization of actual pathology of the vessel wall before luminal narrowing becomes apparent, may help to depict the mechanisms underlying CSVD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Brandhofe and colleagues found that the T2 relaxation time of NAWM was associated with cognition in CSVD patients, which the FA and MD of the NAWM failed to achieve 44 . More recently, newer acquisitions and models such as the free‐water (FW) model have shown greater associations with WM injury and cognitive impairment, as compared to the traditional DTI measures 43 . The development of vessel wall imaging (VWI) allows detailed evaluation of the vessel wall and lumen in a single image setting, enabling the visualization of actual pathology of the vessel wall before luminal narrowing becomes apparent, may help to depict the mechanisms underlying CSVD.…”
Section: Resultsmentioning
confidence: 99%
“…A nine‐year longitudinal study showed that DTI could detect impaired WM microstructure integrity years before WMH become visible on conventional neuroimaging. DTI‐derived parameters, such as fractional anisotropy (FA) and mean diffusivity (MD), have been shown to be associated with cognitive impairment, gait disorders, risk of mortality, and CSVD severity 43 . However, Brandhofe and colleagues found that the T2 relaxation time of NAWM was associated with cognition in CSVD patients, which the FA and MD of the NAWM failed to achieve 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring in detail state-of-the-art MRI techniques in cSVD is beyond the scope of this chapter, for which the reader is referred to recent reviews on the subject. 124,125 As previously discussed, NVU dysfunction is considered an early and pivotal step in the pathogenesis of SVD 126 associated with BBB leakage, impairment of cerebrovascular reactivity and hypoperfusion. Therefore, MRI techniques capable of detecting these early pathological changes are considered promising for mechanistic studies and application as secondary endpoints in future clinical trials.…”
Section: Advanced Mri Techniquesmentioning
confidence: 99%
“…Other methods for analyzing diffusion data are beyond the scope of this review, for which the reader is encouraged to refer to other detailed reviews. 125,213…”
Section: Introductionmentioning
confidence: 99%